2020
DOI: 10.1111/eip.12914
|View full text |Cite
|
Sign up to set email alerts
|

Selection for psychosocial treatment for youth at clinical high risk for psychosis based on the North American Prodrome Longitudinal Study individualized risk calculator

Abstract: Aim Recent findings suggest that family‐focused therapy (FFT) is effective for individuals at clinical high‐risk for psychosis (CHR‐P). As outcomes of CHR‐P individuals are quite varied, certain psychosocial interventions may be differentially effective in subgroups. The present study examined change in positive symptoms for CHR‐P individuals at different levels of predicted risk for conversion to psychosis who received either FFT, a brief form of family education termed enhanced care (EC) or treatment as usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…Importantly, our pilot intervention does include a wider age range of 13-18 which may also be a limitation to the study. This age range is in line with the age ranges in CHR studies (114,115). Furthermore, while the intervention is intended to target clinical heterogeneity and we see this as a strength of this approach, targeting heterogeneity (e.g., taking a broader approach to intervention, teaching skills for several psychological processes) in the sample may also be a limitation that could impact recruitment and results.…”
Section: Additional Considerations For Future Work and Limitationssupporting
confidence: 89%
“…Importantly, our pilot intervention does include a wider age range of 13-18 which may also be a limitation to the study. This age range is in line with the age ranges in CHR studies (114,115). Furthermore, while the intervention is intended to target clinical heterogeneity and we see this as a strength of this approach, targeting heterogeneity (e.g., taking a broader approach to intervention, teaching skills for several psychological processes) in the sample may also be a limitation that could impact recruitment and results.…”
Section: Additional Considerations For Future Work and Limitationssupporting
confidence: 89%
“…One way to overcome this is to incorporate some measure of an individual's outcome likelihood into clinical trial design and analysis. A recent study incorporated predicted risk of conversion (15) into re-examining the efficacy of FFT and found that higher risk individuals showed greater APS improvement with the FFT intervention as compared to the control group, but lower risk individuals showed no difference in APS improvement between the two intervention groups (91). A concrete step toward improving our understanding of effective interventions would be to similarly re-examine results of existing trials by incorporating conversion risk as either a measure of stratification or as a covariate in predicting the trial outcome.…”
Section: Gaps and Future Directions In Preventionmentioning
confidence: 99%
“…Understanding an individual's probable trajectory is most helpful when there is a chance to intervene and potentially improve this trajectory. Approaching this goal could be relatively straightforward [e.g., adding risk scores to clinical trial outcome analysis or stratification (91)], although expanding the scope of inquiry and methods used to interrogate relevant questions will help support the effort to leverage predictive analytics toward improving outcomes.…”
Section: Future Directions Of Inquirymentioning
confidence: 99%
“…In secondary analyses of the NAPLS trial, Worthington et al (2021) found that CHR participants who scored higher on a baseline measure of risk of psychosis conversion—with more severe APS, recent functional deterioration, and cognitive impairment—showed greater reductions in APS in FFT‐CHR than high‐risk individuals in brief psychoeducation or low‐risk individuals in either treatment. Individuals with higher psychosis risk may be more vulnerable to (or may provoke) higher levels of family criticism and conflict than those with lower risk, and may be more likely to benefit from treatments that aim to enhance family relationships.…”
Section: Introductionmentioning
confidence: 99%